Fat embolism and sperm whale ship strikes - Arregui Gil, Marina; Bernaldo De Quirós Miranda, Yara; Saavedra Santana, Pedro; Sierra Pulpillo, Eva María; Suarez Santana, Cristian Manuel; Arbelo Hernández, Manuel Antonio; Diaz Delgado, Josue; Puig Lozano, Raquel Patricia; Andrada Borzollino, Marisa Ana; Fernández Rodríguez, Antonio Jesús (2019)
The Canary archipelago is a geographical area with an important overlap between cetaceans and maritime trafﬁc. Among different species, sperm whales (Physeter macrocephalus), currently listed as a vulnerable species, are the most affected by ship strikes in the Canaries. Subcutaneous, muscular and visceral extensive hemorrhages, and hematomas, indicate unequivocal antemortem trauma. However, when carcasses are highly autolyzed, distinguishing if the trauma have occurred ante- or postmortem can be very challenging. In other species, the presence of fat emboli within the lung